2019
DOI: 10.1186/s12909-019-1900-8
|View full text |Cite
|
Sign up to set email alerts
|

Self-perceived competencies in the diagnosis and treatment of mental health disorders among general practitioners in Lima, Peru

Abstract: AimTo assess the self-perceived competencies in diagnosing and treating patients with mental health disorders, among recently graduated general practitioners (GPs) from Lima, Peru.MethodsA cross-sectional study was performed in April 2017 at a General Practitioner’s meeting held for those who were going to perform the social service, by the Peruvian College of Physicians in Lima. Attendees were invited to answer a questionnaire that evaluated their self-perception of competence in diagnosing and treating four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…This was reported in a self-perception survey that evaluated the competence of Peruvian general practitioners in diagnosing and treating major depression, anxiety disorder, alcohol dependence, and schizophrenia. 56 It is reported that of the 434 responders, 70.5% believed they were competent in diagnosing depression, 73.3% for anxiety, 67.6% for alcohol dependence, 62.0% for schizophrenia, and when the four mental disorders were combined, only 41.6% of participants self-perceived competence in providing an adequate diagnosis. 56 These results highlighted the need to improve medical education so as to develop the skills necessary to confront mental health disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was reported in a self-perception survey that evaluated the competence of Peruvian general practitioners in diagnosing and treating major depression, anxiety disorder, alcohol dependence, and schizophrenia. 56 It is reported that of the 434 responders, 70.5% believed they were competent in diagnosing depression, 73.3% for anxiety, 67.6% for alcohol dependence, 62.0% for schizophrenia, and when the four mental disorders were combined, only 41.6% of participants self-perceived competence in providing an adequate diagnosis. 56 These results highlighted the need to improve medical education so as to develop the skills necessary to confront mental health disorders.…”
Section: Discussionmentioning
confidence: 99%
“…56 It is reported that of the 434 responders, 70.5% believed they were competent in diagnosing depression, 73.3% for anxiety, 67.6% for alcohol dependence, 62.0% for schizophrenia, and when the four mental disorders were combined, only 41.6% of participants self-perceived competence in providing an adequate diagnosis. 56 These results highlighted the need to improve medical education so as to develop the skills necessary to confront mental health disorders. 56 There is a very limited number of studies that have assessed mental health in the general public and healthcare workers in Peru, and, to the best of our knowledge, this study is the first to report the mental health of healthcare workers in Peru during the COVID-19 outbreak.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, we performed a Kruskal Wallis test to evaluate the differences between the perceived importance across domains from the Likert scale, as was done in a previous study [ 43 ]. To do so, we coded the four possible answers: 4 = very important, 3 = somewhat important, 2 = not very important, and 1 = not at all important.…”
Section: Methodsmentioning
confidence: 99%
“…Mais uma vez, exploram-se de forma preponderante os aspectos biológicos. A cobrança excessiva de tratamento farmacológico pode fazer com que os clínicos gerais recém-formados, apesar de reconhecerem e diagnosticarem corretamente os transtornos mentais em geral, sintam-se inseguros em prescrever tratamentos não farmacológicos para seus pacientes 16,17 . É importante ressaltar que a SM, especialmente a psiquiatria, representante da área médica, necessita se relacionar com os fatores orgânico e biológico para receber sua credibilidade.…”
Section: Introductionunclassified